Formação continuada de professores de história no programa nacional dolivro didático - Marcos Antonio Silva (2014)
The aim of this research was the proposal for teachers ongoing educational development that was devised by the Ministry of Education in the Teacher's Guides embodied in the approved textbooks for the National Program of Textbooks (PNLD). We sought to identify which was the profile of the History teacher for Basic Education, and especially what kind of teacher is to be shaped in this program. To answer this question we analyzed the program PSA (Public Service Announcement) and Guide books. The PSAs present regulations and determinations for enrollment, participation and selection of the works in the program. The textbooks guides contained the works approved within the results of the assessments, including considerations on the Teacher's Guide, furthered by specialists, mostly researchers from universities and federal educational institutions. To define the time frame, we decided to adopt the reference document Recommendations for a public policy of textbooks in Brazil, published in 2001, which established a landmark in the process of evaluating/assessing textbooks in PNLD. Despite the breadth of the program, the issues regarding the final years of primary school, in other words, versions 2005, 2008, 2011 and 2014, were chosen. The categories of Backhtins discourse analysis and Roger Chartiers protocols supported the analysis of the document corpus. Among other issues, it was concluded that in the first predominant PSAs a formative perspective aimed at technical teachers focused on reproducing only. In the last two, concerning a polysemic discourse, there are significant contributions towards formation of reflective teachers. In the textbooks guides there is a prevalent reproductive technical perspective on the 2005, 2008 and 2014 issues. The 2011 version, in turn, was the one closer to the prospect of a reflective teacher. In this regard, it is possible to note that there is a direct correspondence between the PSAs and textbooks guides.